2020
DOI: 10.1186/s12935-020-01415-4
|View full text |Cite
|
Sign up to set email alerts
|

Linc00473 potentiates cholangiocarcinoma progression by modulation of DDX5 expression via miR-506 regulation

Abstract: Background: Cholangiocarcinoma (CCA) is a mortal cancer with high mortality, whereas the function and mechanism of occurrence and progression of CCA are still mysterious. Long non-coding RNAs (lncRNAs) could function as important regulators in carcinogenesis and cancer progression. Growing evidences have indicated that the novel lncRNA linc00473 plays an important role in cancer progression and metastasis. However, its function and molecular mechanism in CCA remain unknown. Methods: The linc00473 expression in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…We excluded ( n = 202) studies based on our eligibility criteria. Therefore, ( n = 56) full‐text articles were reviewed, and ( n = 33) studies were included finally 14–46 . Figure 1 represents the PRISMA flowchart and the reasons for exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…We excluded ( n = 202) studies based on our eligibility criteria. Therefore, ( n = 56) full‐text articles were reviewed, and ( n = 33) studies were included finally 14–46 . Figure 1 represents the PRISMA flowchart and the reasons for exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…In different tumors, LINC00473 may play a regulatory role by crosstalk with different miRNAs. Previously reported LINC00473 competitively binding and regulated miRNAs include miR-34a 25 , miR-198 26 , miR-497 27 , 29 , miR-374a-5p 30 , miR-195 32 , 38 , miR-29a-3p 34 , miR-506 35 , and miR-15a 37 , etc. In our study, miR-502-3p was identified as the target miRNA of LINC00473, and its expression is negatively correlated with LINC00473 and tumor invasiveness in PA.…”
Section: Discussionmentioning
confidence: 96%
“…Until now, numerous studies have found that LINC00473 plays an oncogene role in multiple tumors, including glioma 22 , 23 , Wilms tumor 24 , cervical cancer 25 , breast cancer 26 28 , esophageal squamous cell carcinoma 29 , 30 , lung cancer 31 , hepatocellular carcinoma 32 34 , cholangiocarcinoma 35 , gastric cancer 36 , colorectal cancer 37 , pancreatic cancer 38 , and mucoepidermoid carcinoma 39 , etc. It is closely related to tumor proliferation, migration, invasion, and chemo/radio-resistance, and its high expression indicates a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 38 ] Research by Huang also demonstrated that the oncogenes and tumorigenesis roles of LINC00473 are involved in cholangiocarcinoma growth and metastasis by regulating miR-506, which indicated that LINC00473 could be a molecular target for the treatment of cholangiocarcinoma. [ 39 ] Previous study confirmed that the Wnt/β-catenin signaling pathway is of significant importance to the migration and invasion of tumors. [ 40 ] What’s more, Han’s study recommended the downregulation of lncRNA LINC00473 to attenuate the radioresistence of head and neck SCC cells through inhibiting Wnt/β-catenin signaling pathway.…”
Section: Disscusionmentioning
confidence: 94%